Respostas

2014-04-28T21:17:02-03:00
Nas equações de 1° grau sempre isola a incógnita (letra), então:

a)3x+7=x-3                         c)2(x-1)=√7+x
  3x-x=-3-7                             2x-2  =√7+x
    2x =-10                              2x-x=√7+2
      x=-10                                  1x=√7+2
         ¨¨¨¨¨¨                                   x=√7 + 2
           2                                         ¨¨¨¨¨¨¨¨¨¨
       x= -5                                           1
                                                   x= √7 + 2


b)4x-1=3x+√2                          d)2(x-1)-2(x-2)=-(x-3)
   4x-3x=√2+1                             2x-2-2x+4 = -x+3
       1x =√2+1                             2x-2x+x = 3+2-4
         x= √2+1                                      1x = 1
             ¨¨¨¨¨¨¨¨¨¨                                       x = 1
                 1                                               ¨¨¨¨
¨                                                                   1
         x=√2                                               x = 1




Espero ter ajudado, ok.

9 3 9